The Wage-Price Spiral : Industrial Country Evidence and Implications - Kandil, Magda (Washington, D.C. : International Monetary Fund, 2003)
Using quarterly time-series data for a sample of twelve industrial countries, the paper investigates the dynamics of nominal wage and price adjustments in the face of aggregate demand shocks. The evidence illustrates patterns of the wage-price spiral and accompanying fluctuations. During economic expansions, the overlap of nominal adjustments in labor and product markets prolongs output expansion while maintaining or increasing the standard of living. In contrast, structural and institutional settings appear to have moderated the severity of the effects of contractionary demand shocks on real output growth and the standard of living in the variety of countries under investigation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet